Development of CRISPR/Cas9 systems to induce targeted mutations in the promoter region of the OsSRFP1 gene in rice - Khanh Linh, Ly; Van Doai, Nguyen; Thi Linh, Nguyen; Quyen, Phan; Hoang Ha, Chu; Bich Ngoc, Pham; Tien Phat, Do (Vietnam Journal of Biotechnology, 2023)
Rice is one of the most important staple food crops worldwide, especially in Asia. However, the climate change has been negatively affecting the arable land area, which leads to a severe reduction of the rice yield. In which, the salt stress is considered as one of the most critical abiotic stresses. The creation of rice varieties with salt tolerance is an urgent research direction. In this study, we successfully created two CRISPR/Cas9 vectors to introduce targeted mutations of two different positions in the promoter region of the OsSRFP1 , a gene involves in the Ubiquitination pathway and regulates important responses to multiple stresses. Cali from mature seeds of the Khang Dan 18 rice cultivar was used for Agrobacterium mediated transformation. Total 6 T0 rice lines showed CRISPR/Cas9 induced mutations in the targeted sites. Two of them were utilized for validating inheritance and segregation of induced mutations at the T1 generation. Importantly, homozygous mutant lines lacking the transgene were successfully identified at the T1 generation. These mutant lines are valuable materials for us to continue to assess gene expression, plant growth and development as well as salt tolerance in the further research work.